2005
DOI: 10.1080/01457630590890049
|View full text |Cite
|
Sign up to set email alerts
|

Fouling Characteristics of a Light Australian Crude Oil

Abstract: Aimralian crude oil.s. which generally contain little asplmltcne.s. nevcrihcless give rise to fouling in refinery pre heat trains. In this research, the fouling of a 'ieries of such crude oils and their blends is being assessed. The present work focuses on thermal folding resulting from heating Gippsland crude oil at moderate temperanires. The oil is maintained under nitrogen at a pressure of379kPa and re-circulated at bulk temperatures of 80-120''C through an electrically heated annular probe at velocities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 1 publication
4
35
1
Order By: Relevance
“…Therefore, higher fluid velocities will favor less mass deposition and fouling rates. Various experimental studies have been performed to investigate the effects of flow velocities on coke deposition rate and fouling resistance and reported that the deposition rate and fouling resistance decreases with increased flow velocities [41][42][43]. The present CFD simulation results were also observed to follow the same trend with experimental studies.…”
Section: Resultssupporting
confidence: 78%
“…Therefore, higher fluid velocities will favor less mass deposition and fouling rates. Various experimental studies have been performed to investigate the effects of flow velocities on coke deposition rate and fouling resistance and reported that the deposition rate and fouling resistance decreases with increased flow velocities [41][42][43]. The present CFD simulation results were also observed to follow the same trend with experimental studies.…”
Section: Resultssupporting
confidence: 78%
“…An increase in surface temperature increases the fouling rate exponentially which is observed in all mechanisms [13][14][15][16][17]. However, the effect of bulk temperature has contradicting observations with Lambourn and Durrieu [18], Fuhr et al, [19], Storm et al [20].…”
Section: Fouling With Crude Oilmentioning
confidence: 85%
“…Others observe, are the increase in the fouling rates with the fluid temperature [10,11]. Radhakrishman et al [12] developed a predictive model using statistical methods which can a priori predict the fouling rate and decrease in heat exchanger efficiency.…”
Section: Introductionmentioning
confidence: 99%